Radiation dose to the paediatric undergoing diagnostic coronary angiography and percutaneous intervention procedures. (February 2020) - Abuzaid, M.; Abdelrazig, A.; Sulieman, A.; Alkhorayef, M.; Babikir, E.; Alonazi, B.; Bradley, D.A.
Abstract: Successful diagnostic and clinical outcomes in use of interventional cardiac imaging procedures make them strong choices in dealing with cardiovascular disease. Interventional procedures in developing countries are now growing markedly, increasing with the availability of equipment and trained staff. Present study in Sudan has examined pediatric radiation doses during Diagnostic Coronary Angiography (DCA) and Percutaneous Intervention Procedures (PCI), identifying relationships leading to high values, in particular with patient characteristics and exposure parameters. Retrospective data analysis from DCA cases (n = 9) and PCI (n = 48) examined patient-based characteristics, exposure parameters and the Kerma Area Product (KAP). For DCA and PCI, the mean KAP and fluoroscopic time were 4372.4 ± 3190.1 and 3877.6 ± 1249.1 cGy cm 2 and 5 ± 4.7 and 5.3 ± 3.6 min respectively, with correlations between KAP and weight and KAP and fluoroscopic time of r = 0.91 and r = 0.71 respectively. The radiation dose for children during DCA and PCI is a critical issue, avoidable radiogenic risk, needing to be mitigated through optimization. Highlights: Pediatric radiation dose is a critical issue and should be optimized. Radiation dose benchmark guideline should be available to achieve ALARA. Monitoring of radiation dose and awareness improvement among healthcare workers.